Metodologi Imam Ahmad bin Hanbal dalam Menilai Kredibilitas Perawi Hadis - Azzahra, Arini Nabila; Arifin, Tajul (Darul Yasin Al Sys, 2024)
The existence of the sanad in a hadith occupies a crucial position. This is because a hadith is said to be authentic if the line of transmission and the transmitter (narrator) are free from defects. The narrators here become one of the the influential ones in bringing the hadith to a high degree by looking based on intellectual andbehavioral credibility. Intellectuality is a measurable aspects, but every hadith scholar has varied criteria and methods in determining the credibility of a narrator. Imam Ahmad, as one of the leading scholars in the tradition of hadith, has a structured approach in assessing narrators who narrate traditions that are the basis of religious teachings. This article discusses and reviews in detail how Imam Ahmad ibn Hanbal assesses the intellectual credibility of hadith narrators. This research uses a qualitative method with an analytical descriptive approach and data collection techniques in the form of library research. The results of this study found that the methodology used by Imam Ahmad bin Hanbal reflects wisdom, justice and balance in assessing the credibility of narrators. The method used by Imam Ahmad covers various aspects including the testimony of scholars, the compatibility of the narration with the narration of other reliable narrators, and the assessment based on the frequency of the narrator’s mistakes as well as the emphasis on written records and strong memorization also characterize Imam Ahmad’s methodology. This article provides an in-depth insight into Imam Ahmad’s approach in assessing the intellectual credibility of hadith narrators and serves as areference in the future development of evaluation in the study of hadith narration.